Information as a strategic resource intechnology-based companies - Aportela Rodríguez, Ivett M.; Gallego Gómez, Cristina (Revista General de Información y Documentación, 2015)
Information is a strategic resource in technology-based companies. But often its value is not recognized, meaning it is not enhanced nor managed effectively, endangering the development and even survival of these organizations. This article analyzes the descriptions in the literature of how such companies view information as a strategic resource, to provide an initial approach to the topic. A summary of the most important results, and a broad view of the state of the art are given. Technology-based companies and information used in them is characterized, the impact of information in these companies is described, and the role of Science and Technology Parks as mediators in information use is analyzed.
Keywords: Competitive intelligence; Information; Information management; Knowledge; Technology-based companies